A novel computational fluid dynamic method and validation for assessing distal cerebrovascular microcirculatory resistance. (March 2023) - Raynald,; Zhao, Xi; Meng, Linghsuan; Tong, Xu; Xu, Xiaotong; Wang, Wenxin; Miao, Zhongrong; Mo, Dapeng
Highlights: This study developed novel computational strategies that allowed us to estimate the blood flow and resistance distal to the stenosis by using CFD simulation. Our computational strategy may serve as an effective approach to evaluate the actual reference values of microcirculatory resistance. Individualized assessment of non-invasive flow resistance is necessary for the accurate determination of non-invasive cerebrovascular pressure. Abstract: Background and objective: The non-invasive assessment of microcirculatory resistance could improve the treatment of cerebrovascular stenosis. This study aimed to validate a novel computational strategy for determining the reference value of microcirculatory resistance in patients with cerebrovascular stenosis. Methods: We reconstructed a patient-specific 3-dimensional model of the extracranial-intracranial arteries. A computational strategy incorporating patient-specific pressure-wire measurements was developed to estimate the blood flow rate and microcirculatory resistance. Throughout the computational fluid dynamics (CFD) simulation, the boundary conditions were adjusted according to the developed algorithm. Pearson correlation and Bland-Altman analyses were used to quantify the correlation and agreement between CFD calculations and transcranial Doppler (TCD) assessment. Results: A strong correlation was found between the CFD-based and invasive distal pressure measurements ( P <0.0001). Meanwhile, the CFD and TCD-based flow measurements were highly correlated ( r  = 0.853; P  = 0.001). Furthermore, there was a correlation between the mean velocity measured by CFD and the mean velocity measured by TCD ( r  = 0.777; P <0.001). Good agreement was observed between the mass flow by CFD simulation and volumetric flow by TCD ( P  = 0.0266, mean difference: -0.7814 mmHg, limits of agreement, -4.0905 - 2.5276). However, the mean velocities from CFD simulation were in less agreement with those from the TCD assessment ( P  = 0.3992, mean difference, -0.0485; limits of agreement, -0.6141 - 0.5170). Results of the CFD simulation indicate that the flow resistance varies greatly between individuals. Conclusions: The computational strategy of incorporating patient-specific pressure-wire measurements may serve as an effective approach to evaluate the actual reference values of microcirculatory resistance. In addition, an individualized assessment of non-invasive flow resistance is necessary for the accurate determination of non-invasive cerebrovascular pressure.